PENYELENGGARAAN PELAYANAN PUBLIK BERDASARKAN UNDANG-UNDANG TENTANG PELAYANAN PUBLIK DI KECAMATAN MEMPURA KABUPATEN SIAK - Ardiansah; Andrizal (Universitas Lancang Kuning, 2019)
This community service activity was carried out by the Lecturer Team of the Faculty of Law at Lancang Kuning University in the Hall of the District Office of Mempura District, Siak Regency. The purpose of this activity is for public service providers to understand their rights and obligations under the Public Service Act. This legal education uses the lecture method. Counseling that began filling out the pre-test questionnaire and after the question and answer ended the filling of the post-test questionnaire. The results of this activity showed that participants understood the Law on Public Services, understood the obligation to serve every citizen to fulfill their basic rights and needs, and understood the rights of the community to be involved in overseeing public service delivery. Therefore, the Regional Government needs to intensify the implementation of legal counseling about public services.